Pengembangan Desain Pola Islam Muqarnas pada Media Virtual Reality dengan Pendekatan Multisensori - Filly Christalia (Universitas Multimedia Nusantara, 2022)
Patterns that are commonly found in everyday life sometimes have an important role, such as being an aesthetic symbol that has meaning from the thing it represents. Based on this important role, research is produced that develops pattern designs into innovative designs by involving multi-sensory design studies obtained from an interdisciplinary process of design and neuroscience. The purpose of pattern development in this study is to convey the hidden symbols that the pattern has and improve the consumer experience of the pattern design. The research focuses on one of the basic patterns of Islamic geometric decoration which is applied to the muqarnas dome, whose pattern was developed using the image and sound method. The development of the pattern with the image method will use the concept of color-tone synesthesia, while the development of the image method will involve the application of three-dimensional patterns into the immersive media design, virtual reality. Through these two methods, the pattern developed can improve the visual and audio experience of consumers, namely by providing a sensation of the dimensions of space and music that represent the meaning of the color of the pattern. Keywords: design; innovative pattern; multi-sensory design; islamic pattern; synesthesia.